The Underutilization of Lifestyle Modifications in Primary Care Medicine - Jean-Marc Lucas; Karl F. Kozlowski (Sapientia Publishing Group, 2019)
Chronic disease accounts for the majority of deaths in the United States and is often attributed to obesity. A sedentary lifestyle and poor nutrition are primary contributing factors to the development of obesity and thus chronic disease. Primary care providers are optimally positioned to prescribe exercise and nutrition (lifestyle medicine) as a treatment for chronic disease. Unfortunately, this opportunity seems to be regularly lost. Primary care providers often rely too heavily on weight loss pharmaceuticals and bariatric surgeries to treat obesity. This treatment approach however also does little to prevent and treat the accumulation of chronic diseases. The purpose of this review was to evaluate the efficacy of conventional medical weight loss treatments and determine why primary care providers may not prescribe exercise and nutrition more frequently. Our findings suggest that some primary care providers may be uncomfortable prescribing lifestyle medicine as they receive little formal education in this field. In conclusion, prescription of exercise and nutrition by primary care providers may elicit greater long-term weight loss than current medical weight management practices. Medical management is most likely effective when combined with lifestyle medicine. We propose that primary care providers be better trained in lifestyle medicine through their formal and clinical education. Rates of chronic disease accumulation may potentially decrease if providers prescribe lifestyle medical treatments more frequently.